Cost-Effectiveness Analysis of Dapagliflozin Plus Standard Treatment for Patients With Type 2 Diabetes and High Risk of Cardiovascular Disease in China - Kaiyu Huang; Kaiyu Huang; Yao Wang; Yao Wang; Sijia Sun; Sijia Sun; Qian Zhu; Weifeng Zhou; Jiatao Liu; Dongchun Zhu; Xuefeng Xie; Xuefeng Xie (Frontiers Media S.A., 2022)
PurposeTo evaluate the long-term cost-effectiveness of dapagliflozin, in addition to standard treatment, for the treatment of adult patients with type 2 diabetes (T2DM) at high cardiovascular risk from the Chinese healthcare system perspective.MethodsA decision-analytic Markov model with one-year cycles was developed to evaluate the health and economic outcomes in patients with T2DM and high risk of cardiovascular disease (CVD) treated with standard treatment and dapagliflozin plus standard treatment for 30 years. Clinical data, cost, and utility data were extracted from databases or published literature. Quality-adjusted life-years (QALYs), costs (€/¥ 2021) as well as incremental cost-effectiveness ratios (ICERs) were calculated. Deterministic and probabilistic sensitivity analyses were performed to assess the uncertainty in the results.ResultsCompared with standard treatment, dapagliflozin plus standard treatment was predicted to result in an additional 0.25 QALYs (12.26 QALYs vs. 12.01 QALYs) at an incremental cost of €4,435.81 (¥33,875.83) per patient. The ICER for dapagliflozin plus standard treatment vs. standard treatment was €17,742.07 (¥135,494.41) per QALY gained, which was considered cost-effective in China compared to three times the GDP per capita in 2021 (€31,809.77/¥242,928). The deterministic and probabilistic sensitivity analyses showed the base-case results to be robust.ConclusionsThe study suggests that, from the perspective of the Chinese health system, dapagliflozin plus standard treatment is a cost-effective option for patients with T2DM at high cardiovascular risk. These findings may help clinicians make the best treatment decisions for patients with T2DM at high cardiovascular risk.